Remote laboratory experiment access via an RFID interface - Grout, Ian; Murphy, Ciara; Da Silva, Alexandre César Rodrigues [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
In this paper, remote laboratory experiment access is considered through the use of radio frequency identification (RFID) technology. Contactless smart cards are used widely in many applications from travel cards through to building access control and inventory tracking. However, their use is considered here for access to electronic engineering experimentation in a remote laboratory setting by providing the ability to interface experiments through this contactless (wireless) connection means. A case study design is implemented to demonstrate such a means by incorporating experiment data onto a contactless smart card and accessing this via a card reader and web server arrangement. © 2012 IEEE.
Keywords: experimentation; Remote laboratory; RFID; Card readers; Contact less; Contactless smart card; Experiment data; Inventory tracking; Radio frequency identification technology; Remote laboratories; Study design; Web servers; Access control; Laboratories; Radio frequency identification (RFID); Smart cards; Experiments